A cross-sectional study on the factors influencing drug resistance in clinical Mycobacterium tuberculosis in Hulunbuir, Inner Mongolia - Guo Huijun; Yu Yanqin; Hao Jinqi; Zhang Lan; Hao Mingyuan (Srpski Arhiv za Celokupno Lekarstvo)
Introduction/Objective. This study aimed to improve the understanding of drug-resistant tuberculosis (TB) by conducting a retrospective analysis of clinical data from TB patients in Hulunbuir, Inner Mongolia, collected between 2015 and 2017. Methods. A retrospective analysis was performed on clinical data from patients with TB. The data were used to determine monodrug resistance rankings for ethambutol, isoniazid, rifampicin (RIF), and streptomycin. Additionally, the study examined drug resistance rates for multidrug resistance (MDR) combinations, specifically isoniazid + RIF + streptomycin and isoniazid + RIF + ethambutol + streptomycin. A multivariate logistic regression analysis was conducted to assess risk factors for drug resistance, including sex, hospitalization status, age, and treatment history. Results. The findings revealed that both MDR combinations had resistance rates of 4.51%, the highest among the combinations analyzed. Ethambutol, isoniazid, and RIF showed the three highest monodrug resistance rates. Patients undergoing retreatment had higher rates of monodrug resistance, MDR, and polydrug resistance compared with those receiving initial treatment. The multivariate logistic regression analysis indicated that women had a lower risk of developing drug resistance than men, and hospitalized patients were found to be at lower risk than outpatients. Being 20–40 years old and undergoing retreatment were identified as significant risk factors for developing drug-resistant TB. Conclusion. In the Hulunbuir region of Inner Mongolia, there was a notable presence of drug resistance among patients with TB, with specific demographic and treatment history factors contributing to this resistance. These findings underscore the importance of considering these factors in developing targeted treatment strategies and public health policies to combat drug-resistant TB.